The Influence of Religiosity and Social Support on Students' Attitudes toward The Arabic Language - Sidik, Jafar; Zainal Arifin Ahmad; Rahmawati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
The main questions asked include: (1) How religious are the students at MTs Negeri 3 Sleman? (2) What is the social support system for them? (3) How are students' abilities in Arabic? (4) How big is the influence of religiosity on students' Arabic language attitudes? (5) How much influence does the social environment have on students' Arabic language skills? (6) How do religiosity and social support influence Arabic language skills simultaneously? The method used was quantitative analysis with a sample of 223 students from classes VII, VIII and IX. Data was collected using religiosity, social and attitude scales in Arabic, then analyzed using multiple regression via SPSS version 23. The results showed that: (1) 35% of students were classified as minorities in terms of religiosity. (2) The students' social environment is in the medium category (37.2%). (3) Students' Arabic language skills are relatively low, with 43.5% of students in this category. (4) Religiosity has a positive correlation with Arabic language attitudes with a contribution of 28.9%. (5) The social environment has a positive effect on Arabic language skills with a contribution of 33.4%. (6) Simultaneously, religiosity and social support have a positive effect on Arabic language skills with a contribution of 39.8%. This research shows the important role of religiosity and social support in influencing students' Arabic language skills at MTs Negeri 3 Sleman.